The Influence of Product Quality, Service Quality, Price, and Consumer Trust on Repurchase Intention for Household Appliance Products - Iza Muzaki Anwar Rosid; Albari Albari (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of product quality, service quality, price, and consumer trust on the repurchase intention of household products at Ananda Company, referring to the Theory of S-O-R (Stimulus-Organism-Response). S-O-R theory explains that product quality, service quality, price, and consumer confidence act as external stimuli that affect consumers' internal conditions in the form of consumer confidence representing the organism, which then produces a response in the form of repurchase intentions. This study employs a quantitative method using the Structural Equation Modeling (SEM) technique. Data were collected through a questionnaire distributed to 300 respondents. The results indicate that three hypotheses are supported, while four hypotheses are not supported. Service quality has a positive and significant effect on repurchase intention, product quality has a positive and significant effect on consumer trust, and consumer trust has a positive and significant effect on repurchase intention. However, service quality and price do not have a positive and significant effect on consumer trust, and price does not have a positive and significant effect on repurchase intention.